2010
DOI: 10.3171/2010.7.gks10857
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife surgery in the management of orbital tumors

Abstract: Object The authors evaluated the results they obtained using Gamma Knife surgery (GKS) in patients with orbital tumors. Methods This is a retrospective clinical evaluation of 202 patients with orbital tumors who were treated with GKS between September 1995 and October 2008. The series included 84 men and 118 women with a mean age of 39.5 ± 14.6 years (range 5–85 years). The diagnoses were determined based on pathological analyses in 113 patients and presumed based on characteristic clinical and imaging findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In the Xu et al study, 22 202 patients with orbital tumors underwent Gamma Knife surgery. While the tumor was smaller in 58.4% of patients, it remained stable in 35.1%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Xu et al study, 22 202 patients with orbital tumors underwent Gamma Knife surgery. While the tumor was smaller in 58.4% of patients, it remained stable in 35.1%.…”
Section: Discussionmentioning
confidence: 99%
“…5,8,16 Few studies have shown the effectiveness of stereotactic Gamma Knife surgery for ONG, and these have a limited number of patients. 16,17,22 To our knowledge, there is only 1 case study documenting neovascular glaucoma after FSRT using the CyberKnife. 14 Thus, in the present study we revealed the clinical findings and effect of FSRT via the CyberKnife on visual acuity and local control in a child with an ONG.…”
mentioning
confidence: 99%
“…Lesions developing in the orbital region often have pathological characteristics similar to those of intracranial tumors, and their biological responses to single high-dose irradiation are predicted to be similar as well, although there are few reports concerning the application of radiosurgery to orbital lesions. 1,8,11,19 However, there is an important difference between orbital and intracranial tumors with respect to radiosurgery. In the treatment of orbital tumors, radiation-sensitive structures such as the optic apparatus are inevitably exposed to substantial irradiation in almost all cases, and this may be a major reason for the undervaluation of radiosurgery.…”
Section: Discussionmentioning
confidence: 99%
“…GammaKnife stereotactic radiosurgery has been used in the treatment of ophthalmic malignancies including uveal melanoma, orbital paraganglioma, choroidal hemangiomas, cranial nerve schwannomas, and choroidal metastases [30,[33][34][35][36][37][38]. The effectiveness and adverse reactions are considered comparable between GammaKnife stereotactic radiosurgery, though dosimetric data suggests protons may confer a slightly decreased risk of second malignancies than photons when life expectancy is many decades [39][40][41][42].…”
Section: Stereotactic Radiosurgery (Gammaknife)mentioning
confidence: 99%